Perception Towards Online Learning Implementations During Covid-19 Pandemic: Comparitive Study Malaysia And Indonesia Students - Nur Najwa Shahlan; Mohamad Aizi Salamat; Shahlan Surat (Applied Information Technology And Computer Science, 2021)
The Coronavirus Disease outbreak (COVID-19) causes a transformation in teaching and learning in universities in Malaysia and Indonesia. Various efforts are being and have been made to overcome this challenging situation. Most universities have made teaching and learning initiatives using online education through e-learning. Therefore, this study’s purpose was conducted to determine the level of perception of the implementation of online learning. The study used a survey study on 370 students consisting of 217 Universiti Tun Hussein Onn Malaysia students and 153 students of Telkom University Bandung Indonesia. The study sample is a Bachelor student of the Faculty of Computer Science and Information Technology (FSKTM) in the Bachelor of Information Technology Universiti Tun Hussein Onn Malaysia and Faculty of Industrial Engineering (FRI) course in the Bachelor of System Information Telkom University. Data were collected using the Perception, Attitudes, And Readiness Toward Online Learning questionnaire by Linjawi and Alfadda. Data were analyzed using the Statistical Package for the Social Sciences (SPSS Ver.26) program using descriptive statistical analysis and inferential statistics, namely t-tests to determine the differences in the level of perception of online learning implementation. Based on the research finding, students from Telkom University Bandung Indonesia have a high level of knowledge technology access, and computer skills. These two universities students have a high level of online skills knowledge and lastly, a moderate level of motivation and support needed. There was a significant difference in technology access and computer skills scores meanwhile There is no significant difference in scores for online skills, motivation, and needed support for Universiti Tun Hussein Onn Malaysia and Telkom University Bandung. In conclusion, regardless of the technological sophistication of a Malaysian or Indonesian educational institution, students’ perceptions of e-learning were instrumental in bolstering the educational process during the COVID-19 pandemic